2006
DOI: 10.1007/bf02969263
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and COX-2 inhibitory constituents from the aerial parts ofAralia cordata

Abstract: Three diterpenes (1, 8, and 9), three triterpenes (3, 4, and 7), one saponin (11), four sterols (2, 5, 6, and 12), and one cerebroside (10) were isolated from the EtOH extract of the aerial parts of Aralia cordata by repeated silica gel column chromatography. Their chemical structures were identified by comparing their physicochemical and spectral data with those published in literatures. All isolated compounds were evaluated for their cytotoxicity against L1210, K562, and LLC tumor cell lines using MTT assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Column chromatography was performed by using silica gel (Kieselgel 70 to 230 mesh and 230 to 400 mesh, Merck), and thin layer chromatography (TLC) was performed on pre-coated silica gel 60 F254 (0.25 mm, Merck). The structure of this compound was confirmed by comparison of spectral data with those reported in the literature (Figure 1) (Lee et al, 2006).…”
Section: Isolation Of Oleanoic Acid 28-o-β-d-glycopyranosyl Ester (Oa)supporting
confidence: 74%
See 3 more Smart Citations
“…Column chromatography was performed by using silica gel (Kieselgel 70 to 230 mesh and 230 to 400 mesh, Merck), and thin layer chromatography (TLC) was performed on pre-coated silica gel 60 F254 (0.25 mm, Merck). The structure of this compound was confirmed by comparison of spectral data with those reported in the literature (Figure 1) (Lee et al, 2006).…”
Section: Isolation Of Oleanoic Acid 28-o-β-d-glycopyranosyl Ester (Oa)supporting
confidence: 74%
“…Although, NF-κB activation is regulated by MAPKs through multiple mechanisms, accumulating evidence indicates that NF-κB activation is modulated by MAPKs that induce sitespecific phosphorylation of an inhibitory protein called IκB (Kim et al, 1997). Activation of NF-κB is dependent on the degradation of IκB, an endogenous inhibitor that binds to NF-κB in the cytoplasm (Lee et al, 2006). In these studies, OA was shown to decrease the degradation and phosphorylation of IκB and nuclear translocation of NF-κB (p65) in PMA plus A23187-stimulated mast cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Diterpenes have been elucidated as analgesic and anti-inflammatory agents of this plant root (18,19). In addition to diterpenes, polyacetylenes, a lipid glycerol, and sterols having cyclooxygenase (COX) inhibitory activity have been isolated from the root (20); and diterpenes, triterpenes, and a saponin have been isolated as COX-1 and COX-2 inhibitors from the aerial part of this plant (21). Since reactive oxygen species (ROS) and inflammation are part of the complex series of pathophysiological events that contribute to neurodegenerative diseases such as AD and stroke (22,23), free radical scavengers and anti-inflammatory agents have attracted considerable attention as potential neuroprotective agents.…”
Section: Introductionmentioning
confidence: 99%